Bentonite-chitosan bionanocomposite for adsorption of used lubricant oil: Bentonit-kitosan - Siregar, Sri Hilma; Nurhaliza, Dwi; Ramadhanti, Aulia Rizki (Acta Chimica Asiana, 2025)
The growth of the transportation industry has led to the expansion of the automotive sector. Automotive business activities have the potential to cause several environmental problems, one of which is environmental pollution caused by used lubricating oil waste. One alternative effort to process lubricating oil waste is the adsorption method. This research aims to determine the ability or effectiveness of bentonite-chitosan composites in adsorbing waste lubricating oil. This research began by synthesizing Bentonite-Chitosan composites. The successfully synthesized material was then characterized using X-ray diffraction (XRD) and Fourier Transform Infra Red (FTIR) instruments. After that, it will be applied to used lubricating oil waste with variations in time and mass variations. The ability of the Bentonite-Chitosan composite to adsorb waste lubricating oil will be seen through the viscosity test results. The viscosity test results show a significant influence on the viscosity of the used lubricating oil. Meanwhile, the results of viscosity testing for mass variations show that the more bentonite-chitosan composite used, the greater the viscosity increase value. The highest viscosity value was obtained in the bentonite-chitosan composite of 15 g with a time of 5 hours at 7,75 cSt.